Pengaruh Relaksasi terhadap Kecemasan dan Kualitas Tidur pada Pasien Intensive Care Unit - Sudiarto Sudiarto; Ari Suwondo; Agus Nurrudin (Poltekkes Kemenkes Semarang, 2015)
The objective of study was to determine the effect of relaxation on anxiety and sleep quality in ICU patients. This study used quasi Experimental research design with Pre and Post test Control Group Design. Sample of this study is ICU patients that were 56 respondents, consisted of 28 respondents provided a relaxation and dzikir intervention and 28 respondents as a control group. Data were analyzed by univariate frequency distribution table, while the bivariate data using paired t-test, Wilcoxon and Mann-Whitney. Research procedures performed by observing and assessing check the level of anxiety and sleep quality before and after intervention. Relaxation dhikr influence the change in the level of anxiety and sleep quality. In the treatment group p-value of 0.001 anxiety levels and sleep quality 0.001, while the p-value control group anxiety levels 0,001 dan 1.00 sleep quality. Independent test anxiety levels p-value of 0.001 and 0.001 sleep quality. Relaxation and dzikir influence the change level of anxiety and sleep quality. In the control group satitistik result there are significant differences, although in severe anxiety kategiori, can relaxation and dzikir be recommended as a nursing intervention to improve the quality of patient sleep and anxiety in hospital.